Code-switching and linguistic borrowing of English language by Taiwanese users in contemporary online discourse - Kuusikorpi, Minka (My University, 2026)
Code-switching is a well-known and studied phenomenon in both spoken and written interactions, however the research on bilingual code-switching involving two different writing scripts is sparse. Furthermore, the rapid increase in use of computer mediated communication and online interaction in everyday situations has changed the ways in which language is used. This study aims to fill some of the gaps in the current literature and to examine how the use of language among Taiwanese online users has changed over time. The goal of this thesis is to examine how users of the Taiwanese online platform Dcard incorporate English language and the Latin script into their Mandarin Chinese discourse. Data was collected over a three-week period from three of the most popular discussion forums on the platform and included 200 posts or comments from each forum. The data was categorized by the type of each item and evaluated on the basis of popular theories regarding the motives for code-switching and previously conducted similar studies on Taiwanese online platforms. The results showed a variety of ways in which users utilized English language and Latin script, the most common types of items being proper nouns and abbreviations. Motives for code-switching were not always clear, but included economical use of language, clarity, and expressions of creativity and personality. Due to the scope of the data pool some motives or factors may have been accidentally overlooked. For future studies focusing on specific types of data or motives could provide further information on the nature of code-switching in contemporary online spaces.
Keywords: code-switching; linguistic borrowing; asynchronous communication; computer-mediated communication; Taiwan